Regulatory mechanisms involved in muscle and bone remodeling during refeeding in gilthead sea bream - Lavajoo, F. (Sci Rep, 2020)
The tolerance of fish to fasting offers a model to study the regulatory mechanisms and changes produced when feeding is restored. Gilthead sea bream juveniles were exposed to a 21-days fasting period followed by 2 h to 7-days refeeding. Fasting provoked a decrease in body weight, somatic indexes, and muscle gene expression of members of the Gh/Igf system, signaling molecules (akt, tor and downstream effectors), proliferation marker pcna, myogenic regulatory factors, myostatin, and proteolytic molecules such as cathepsins or calpains, while most ubiquitin-proteasome system members increased or remained stable. In bone, downregulated expression of Gh/Igf members and osteogenic factors was observed, whereas expression of the osteoclastic marker ctsk was increased. Refeeding recovered the expression of Gh/Igf system, myogenic and osteogenic factors in a sequence similar to that of development. Akt and Tor phosphorylation raised at 2 and 5 h post-refeeding, much faster than its gene expression increased, which occurred at day 7. The expression in bone and muscle of the inhibitor myostatin (mstn2) showed an inverse profile suggesting an inter-organ coordination that needs to be further explored in fish. Overall, this study provides new information on the molecules involved in the musculoskeletal system remodeling during the early stages of refeeding in fish.